A prospective comparison of transvaginal, transabdominal ultrasound and diagnostic curettage in the evaluation of endometrial pathology in Erbil - Sedeq, Media Ghazi; Muhammad, Parez Radham; Shekh Mohammed, Samira S.; Alalaf, Shahla K. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Abnormal uterine bleeding due to endometrial abnormalities is a common diagnostic challenge facing the radiologist and referring gynecologist. This study was aimed to compare the diagnostic performance of transvaginal ultrasound, transabdominal ultrasound and diagnostic curettage in the detection of endometrial pathologies in symptomatic women. Methods: A prospective comparison study of transvaginal ultrasound, transabdominal ultrasound and diagnostic curettage was conducted for evaluation of endometrial pathology in Maternity Teaching Hospital, Erbil city,Kurdistan region of Iraq, from September13th, 2013 to September14th, 2014. The study included 100 women presenting with abnormal uterine bleeding.Ultrasound findings were compared with histopathological results. The statistical package for the social sciences (version 17) was used for data entry and analysis. Results: The mean age (± SD) of sample size was 47 ±8.57 years. The mean parity was 5.17 ± 2.71. The highest percentages of women were in age group 40-59 years (73%). Of the total sample, more than half (52%) had regular cycles, 25% had irregular cycles and 23% were in menopausal state. In more than half of cases the indication for ultrasounds was for menorrhagia, followed by postmenapousal and intermenstrual bleeding (23% and 21%, respectively). Of 98 women (2 women were excluded from analysis), 19% had atrophic endometrium and 67% had endometrial hyperplasia in histopathological finding. Transvaginal ultrasound sensitivity and specificity were 100% and 92.9%, respectively while transabdominal ultrasound sensitivity and specificity were 92.8% and 65%, respectively. Conclusion: Transvaginal ultrasound scanning is an excellent tool for the determination of whether further investigation with histopathological examination of endometrial biopsy is necessary or not for women presented with abnormal uterine bleeding.